The interactive effects of work–family conflict and coping styles on occupational fatigue among endoscopy nurses: a cross-sectional study - Zeng, Zhi; Fu, Chunyan; Zhou, Sumei; Xie, Guiqiong; He, Yazhi; Liu, Meng; Liu, Chao (Frontiers in Public Health, 2025)
BackgroundAlthough work–family conflict and coping styles have been identified as factors influencing nurses’ occupational fatigue, the interactive mechanism between these variables remains unclear among endoscopy nurses. This study, guided by the Job Demands-Resources (JD-R) Model, aims to investigate the interactive effects of work–family conflict and coping styles on occupational fatigue among endoscopy nurses.MethodsA cross-sectional study was conducted from July 1 to July 31, 2024, involving 320 endoscopy nurses from 23 medical institutions across China. Standardized scales, including the Work–Family Conflict (WFC) scale, the Simplified Coping Style Questionnaire (SCSQ), and the Fatigue Assessment Instrument (FAI), were used to measure work–family conflict, coping styles, and occupational fatigue, respectively. Logistic regression models were applied to analyze the associations between variables, and additive interaction indices (RERI, API, SI) were used to test interaction effects.ResultsHigh-intensity work–family conflict (OR = 1.214, 95% CI: 1.143–1.289) and negative coping (OR = 1.209, 95% CI: 1.137–1.285) significantly increased the risk of occupational fatigue, whereas positive coping could reduce the risk of occupational fatigue (OR = 0.800, 95% CI: 0.755–0.848). Interaction analysis indicated that there was a synergistic effect between work–family conflict and negative coping (SI = 1.293, 95% CI: 1.064–1.489), while an antagonistic effect was observed between work–family conflict and positive coping (SI = 0.700, 95% CI: 0.205–1.990).ConclusionWork–family conflict and negative coping jointly exacerbate occupational fatigue among endoscopy nurses through a synergistic interaction, while positive coping may help mitigate these adverse effects. Interventions aimed at optimizing work resource allocation, enhancing adaptive coping training, and improving work-family boundary management are recommended to promote occupational health in this population.